CEO partisan bias and management earnings forecast bias - Stuart, Michael D.; Wang, Jing; Willis, Richard H. (Review of Accounting Studies, 2025)
Research concludes that managers’ political orientation influences their decision-making and offers the political connections and risk tolerance hypotheses as explanations. We investigate partisan bias as an additional way political orientation may influence managers’ decisions. Partisan bias results in individuals whose partisan orientation aligns with that of the US president expressing more optimistic economic expectations. We examine whether partisan bias is present in managers’ annual earnings forecasts. We find that firms with CEOs whose partisanship aligns with that of the US president issue more optimistically biased annual earnings forecasts than firms with other CEOs. Higher-ability CEOs, however, are less susceptible to partisan bias. Additionally, we find that overestimating customer demand contributes to the forecast over-optimism of partisan-aligned CEOs and results in greater firm overinvestment. Furthermore, investors fail to discount the news in forecasts of partisan-aligned CEOs, and their firms’ post-forecast abnormal returns are lower.